Battery lifetime enhancement via smart hybrid energy storage plug-in module in standalone photovoltaic power system. (February 2019) - Jing, Wenlong; Lai, Chean Hung; Ling, Derrick K.X.; Wong, Wallace S.H.; Wong, M.L. Dennis
Highlights: Poor lifetime of the lead-acid battery in standalone photovoltaic power system due to severe generation-demand mismatch. A retrofittable smart hybrid energy storage plug-in module that aims to mitigate battery stress has been proposed. Matlab Simulink model of the proposed system has been developed and simulated to investigate the power-sharing capability. A down-scaled prototype has been developed and tested in the actual standalone photovoltaic-battery power system. Economic analysis shows a battery cost reduction of up to 52.7 % with the integration of the proposed system. Abstract: Standalone photovoltaic power system is one of the feasible solutions in rural electrification. However, due to the intermittent nature of solar energy and significant demand variations due to small load size, energy storage devices are needed to ensure power quality and reliability. Lead-acid battery bank has been widely used in such systems to act as the intermediate buffer to compensate the power mismatch between generation and demand, despite the poor lifetime characteristics and relatively short service life compared to other energy storage devices. Most charge controllers only provide basic battery charging functionality and prevent the battery bank from overcharging and deep-discharging. While other notable aging factors such as frequent charge-discharge transition, high C-rate and surge power are often neglected. This paper presents a smart hybrid energy storage plug-in module that aims to enhance the service life of Lead-acid battery in standalone photovoltaic-battery power systems by mitigating life-limiting factors such as current fluctuations and surge current. This module is designed as a plug-in module that can be adopted directly in existing infrastructure in installed standalone PV-battery power system. The effectiveness of the proposed plug-in module in mitigating battery stresses is simulated in Matlab Simulink with actual solar irradiance data and estimated load profile for a rural community in Sarawak Malaysia. The simulation results are validated experimentally with the scaled-down photovoltaic-battery power system. The effectiveness in mitigating battery stress is quantitatively evaluated with battery health cost function, while the reduction in overall battery cost is analyzed and discussed.